Analysis of Factors Affecting Post Immunization Event (AEFI) of COVID-19 Vaccines in Indonesia: Online Survey - Yeni Indriyani; Cynthia Agustina; Anaelia Syakilla Maharatna; Ameilia Nurhidayastuti; Denny Saptono Fahrurodzi; Tanjung Anitasari Indah Kusumaningrum; Izzatul Arifah; Happy Kusuma Mulya (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Cases of death and infection due to COVID-19 in Indonesia are the highest compared to other countries in Southeast Asia even though there are various types of Covid-19 vaccines in Indonesia. Although the Covid-19 vaccine has several benefits, there are side effects caused by vaccine administration (AEFI). Many studies have been conducted on AEFI of Covid-19 vaccine in the general public, but the number of studies that discuss special groups needs to be studied further. Objective: This research aims to find out AEFI from more diverse community groups so that the results can be used as material for consideration in policy making. Method: This type of research is a quantitative study with a research design using a cross-sectional study design and using the chi-square test. The sample amounted to 656 respondents who were taken using simple random sampling. Data collection was conducted in September 2023 based on a web survey through Google Forms. Questions regarding diet refer to the General Guidelines for Balanced Nutrition, sleep quality refers to the Pittsburgh Sleep Quality Index (PSQI), and anxiety refers to the Hamilton Rating Scale for Anxiety (HARS). Data will be processed using Stata 18 data processing application. Result: There was no correlation between the factors studied and post-immunization adverse events (AEFI). However, history of atopic disease had an effect of 1.355 times greater than the dietary category which only had an effect of 0.725 times. Conclusion: Factors associated with post-immunization adverse events (AEFI) such as socio-demographics, history of illness, diet and breakfast, history of allergic disease, history of atopic disease, history of anxiety, vaccine complaints, post-vaccine reactions did not have a significant association with AEFI.